2005
DOI: 10.1007/s00277-005-1071-z
|View full text |Cite
|
Sign up to set email alerts
|

Randomized study of Helicobacter pylori eradication therapy and proton pump inhibitor monotherapy for idiopathic thrombocytopenic purpura

Abstract: Helicobacter pylori (HP) eradication therapy is a useful treatment for idiopathic thrombocytopenic purpura (ITP). Some investigators have also reported the effects of proton pump inhibitor (PPI) monotherapy on ITP. We performed a randomized study of HP eradication therapy and PPI monotherapy on ITP. Four of nine patients achieved complete remission (CR), two of nine achieved partial remission (PR) in HP eradication therapy, three of eight achieved CR, and two of eight achieved PR in PPI monotherapy. No signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Th ere is evidence from small randomized and non-randomized trials for a sustained improvement in platelet counts aft er eradication of H. pylori infection in a proportion of adult patients with ITP (75)(76)(77). Th e evidence is less compelling for children with ITP ( 78 ).…”
Section: Idiopathic Thrombocytopenic Purpura (Itp)mentioning
confidence: 99%
“…Th ere is evidence from small randomized and non-randomized trials for a sustained improvement in platelet counts aft er eradication of H. pylori infection in a proportion of adult patients with ITP (75)(76)(77). Th e evidence is less compelling for children with ITP ( 78 ).…”
Section: Idiopathic Thrombocytopenic Purpura (Itp)mentioning
confidence: 99%
“…218 Studies have also shown that there is a significant increase in platelet count in patients with ITP after H. Pylori eradication. 220,222,223,224 Prevention of gastric cancer ACG recommends H. Pylori testing after endoscopic resection of early gastric cancer. EHSG recommends H. Pylori testing and eradication in first-degree relatives of patients with gastric cancer.…”
Section: Chronic Itpmentioning
confidence: 99%
“…Patients receiving corticosteroids, antibiotics and immunosuppressive drugs were excluded. Because proton-pump inhibitors [19,20] and non-steroidal anti-inflammatory drugs [21,22,23,24,25,26] could alter the cytokine profile, patients receiving proton-pump inhibitors or non-steroidal anti-inflammatory drugs were also excluded. Smoking habit had been reported to upregulate peripheral platelet counts [7,8,9], and thus, current smokers were excluded.…”
Section: Methodsmentioning
confidence: 99%